(untitled) (Journal of Governance and Development (JGD), 2011)
The study examined the social impact of environmental changes on selected rural communities in Nigeria Niger-Delta. The data were generated from literature materials and oral interview of respondents over a period of 18 months. This touches on social and cultural dislocations, political and ethnic conflicts, as a result of environmental degradation occasioned by oil exploitation and exploration. It concludes that broadening and strengthening rural livelihood as well as concerted efforts by all stakeholders at environmental reclamation and sustainable use of the environment, will go a long way in the social and economic stability of the region in general and the rural communities in particular.